Adjunctive use of intravitreal dexamethasone in presumed bacterial endophthalmitis: a randomised trial. Issue 10 (2nd February 2011) - Albrecht, E; Richards, J C; Pollock, T; Cook, C; Myers, L
Abstract : Aim: To evaluate the use of intravitreal dexamethasone as adjunctive therapy in the treatment of presumed bacterial endophthalmitis. Design: Prospective, double masked, randomised placebo-controlled clinical trial. Methods: Patients with 'post cataract surgery', 'bleb-related' and 'other' endophthalmitis were grouped and randomised to receive intravitreal ceftazidime (2.225 mg/0.1 ml), vancomycin (1 mg/0.1 ml), and either dexamethasone (0.4 mg/0.1) or placebo. All underwent vitreous and aqueous sampling for microbiological analysis. Injections were repeated after 48 h if necessary. The primary outcome measure was Snellen visual acuity on presentation, within the first 14 days post injection, and at 2–4 months. Results: 62 patients completed the protocol from 2001 to 2005. Thirty patients received intravitreal dexamethasone and 32 received intravitreal placebo. There was no statistically significant difference in the visual outcomes of either group with a mean 2.79 Snellen lines improvement of the intravitreal dexamethasone group versus 1.8 lines in the placebo group. Subgroup analysis suggested a clinical trend to better visual acuity in the post cataract steroid subgroup with mean 4.1 lines improvement versus 2.7 in the placebo group (p=0.33). No adverse events attributable to the dexamethasone were reported. Conclusions: Intravitreal dexamethasone appears safe and may be of benefit in post cataract surgery bacterial endophthalmitis.